In Vitro Rumen Fermentation Characteristics and Fatty Acid Profiles Added with Calcium Soap of Canola/Flaxseed Oil - S. Suharti; A. R. Nasution; K. G. Wiryawan (Media Peternakan, 2017)
This research aimed to assess the effect of adding canola oil and flaxseed oil which were protected with calcium soap (Ca-soap) on the fermentation characteristics, rumen microbial population, and the profile of fatty acids in the rumen during 4 and 8 hours in the in vitro fermentation. The research design used in this study was a completely randomized block design with 3 treatments and 4 replications. The treatments consisted of control ration (Napier grass and concentrate at the ratio of 60 : 40), control + 6% of Ca-soap of canola oil, and control + 6% of Ca-soap of flaxseed oil. Variables observed were pH value, NH3 concentration, volatile fatty acid (VFA), dry matter and organic matter digestibility, and fatty acid profile.  The results showed that the addition of Ca-soap of canola or flaxseed oil did not affect the pH value, NH3 concentration, dry matter digestibility, organic matter digestibility, total population of bacteria and protozoa in the rumen. However, the total production of ruminal VFA was increased (P<0.05) with the addition of Ca soap of canola oil/flaxseed oil. The use of Ca-soap of flaxseed oil increased (P<0.05) the content of unsaturated fatty acids in the rumen at 4 h incubation. The addition of Ca-soap of flaxseed oil resulted the lowest (P<0.05) level of unsaturated fatty acids biohydrogenation compared to the other treatments at 4 h incubation. In conclusion, the addition of Ca soap of canola/flaxseed oil could improve VFA total production. Vegetable oils protected using calcium soap could inhibit unsaturated fatty acid biohidrogenation by rumen microbes. Ca-soap of flaxseed oil could survive from rumen biohydrogenation in the rumen better than Ca-soap of canola oil.